35 volunteers from Faculty of Chemical & Natural Resources Engineering gained valuable experience from 2012 World Gas Conference - Md. Noor, Arifin
A total of 35 final-year gas technology programme undergraduates from the Faculty of Chemical & Natural Resources Engineering (FKKSA), Universiti Malaysia Pahang (UMP) were given a special treat for their role in helping to organise the World Gas Conference (WGC) held in Kuala Lumpur Convention Center on June 21, 2012.